Evaluasi Pembelajaran Sains Pada Nilai-Nilai Kejujuran, Kesabaran Di Madrasah Aliyah Negeri Insan Cendekia Halmahera Barat - Latif, Amina; Sangaji, Nurdiana; Pramono, Aji Joko (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to evaluate the implementation of science learning integrated with honesty values in Madrasah Aliyah Negeri Insan Cendekia West Halmahera. Using descriptive qualitative approach, the research was conducted for 6 months by involving various school stakeholders. Data collection techniques included in-depth interviews, participant observation, document analysis, and focus group discussions.The results showed that Madrasah Aliyah Negeri Insan Cendekia West Halmahera has attempted to integrate the value of honesty in science learning through curriculum, learning methods, and the role of teachers. The study concluded that further development is needed in various aspects, including teacher capacity building, consistent integrated curriculum development, and the creation of a school culture that supports scientific integrity. The findings provide important insights for the development of a science learning model integrated with honesty values at the senior high school level in Indonesia.